1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Can someone explain (Differential Forms)

  1. Feb 17, 2009 #1
    (i) if [itex]\alpha=\sum_i \alpha_i(x) dx_i \in \Omega^1, \beta=\sum_j \beta_j(x) dx_j[/itex]

    then[itex]\alpha \wedge \beta = \sum_{i,j} \alpha_i(x) \beta_j(x) dx_i \wdge dx_j \in \Omega^2[/itex]

    NOW THE STEP I DON'T FOLLOW - he jumps to this in the lecture notes:

    [itex]\alpha \wedge \beta = \sum_{i<j} (\alpha_i \beta_j - \beta_j \alpha_i) dx_i \wedge dx_j[/itex]

    the subscript on the sum was either i<j or i,j - could someone tell me which as well as explaing where on earth this step comes from.

    (ii) could someone explain the Leibniz rule for exterior derivative [itex]d: \Omega^k \rightarrow \Omega^{k+1}[/itex]

    i.e. why [itex]d(\alpha^k \wedge \beta^l)=d \alpha^k \wedge \beta^l + (-1)^k \alpha^k \wedge d \beta^l[/itex]
    note that the superscript on the differential form indicates that it's a k form or and l form

    my main problem here is where the (-1)^k comes from

    cheers for your help
  2. jcsd
  3. Feb 17, 2009 #2


    User Avatar
    Science Advisor
    Homework Helper

    Hi latentcorpse! :smile:
    It's i < j …

    [itex]\alpha \wedge \beta = \sum_{i,j} (\alpha_i \beta_j) dx_i \wedge dx_j = \sum_{i<j} (\alpha_i \beta_j - \beta_j \alpha_i) dx_i \wedge dx_j[/itex]

    since wedge is anti-commutative.
    d() is like another wedge, so if you move d() through k elementary forms, you multiply it by (-1)k :wink:
  4. Feb 17, 2009 #3
    cool i get the 2nd part now - still not sure why it's i<j or why [itex]\alpha_i \beta_j[/itex] suddenly becomes [itex]\alpha_i \beta_j-\beta_j \alpha_i[/itex]
  5. Feb 17, 2009 #4


    User Avatar
    Science Advisor
    Homework Helper

    (have an alpha: α and a beta: β and a wedge: ∧ :wink:)
    because αi ∧ βj = -βj ∧ αi

    so if you sum αi ∧ βj over all i and j,

    then for i > j you just "turn it round" :wink:
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook